The Effect of Problem Based Learning Model on Junior High School Students' Problem Solving Ability - Hanifa, Shofia; Afrilianto, Muhammad; Amelia, Risma (IKIP Siliwangi, 2024)
Students have difficultly solving problem in question such as when solving word problrms, asking questions, making steps to solve, and solving problems given. Problem solving skills are a very important part of mathematics curriculum. So the researchers conducted a study that aimed to determine the effect of problem based learning models on problem solving abilities in class VII set material. The development model used is an experimental research type using a quantitative approach. The research data was obtained trough test instruments or scores from the problem solving instrument on set material. Data analysis of problem solving abilities was carried out using the t-test. The subjects of this study were 78 students. The sample was taken by simple random sampling, selected class VII D with a total 10 students as the experimental classs and 10 from class VII E as the control class. The results of this study indicate thet the problem based learning model has an effect on problem solving abilities. This can be seen based on the results of working on essay test question based on students problem solving abilities which get a tcount of 2.5776 while the ttable value is 2.0378. This means that the value of tcount is greater than t table, so in this case it means that H1 is accepted, meaning that there are differences in mathematical problem solving abilities between the experimental class and the control class. This shows that the problem based learning model has an influence on problem solving abilities.